2022
DOI: 10.3389/ffgc.2022.938941
|View full text |Cite
|
Sign up to set email alerts
|

Non-structural carbohydrate and water dynamics of Moso bamboo during its explosive growth period

Abstract: Newly sprouted culm (culm_new) of Moso bamboo can complete its height growth within 1 or 2 months without growing any leaf. This explosive growth without enough leaf photosynthesis may rely heavily on external carbon input, such as carbon storage in the rhizomes or culms from the nearby mother culms (culm_mother). However, the existing studies have not explored the role of new photosynthesized carbon by the nearby culm_mother and the corresponding water dynamics. Therefore, this study monitored non-structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Obviously, the adult culms have more favourable conditions to provide NSCs for bamboo shoots. Due to the water–carbon collaborative transport, the direction of water flow from high to low water potential in the bamboo stand determined the direction of carbon transport [ 19 , 53 ]. During this process, bamboo culms of different ages contributed carbon to the shoots, but we believe that the adult culm contributed more carbon to the system, especially the 3-year-old culm; this might also be influenced by the standing conditions and bamboo stand structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, the adult culms have more favourable conditions to provide NSCs for bamboo shoots. Due to the water–carbon collaborative transport, the direction of water flow from high to low water potential in the bamboo stand determined the direction of carbon transport [ 19 , 53 ]. During this process, bamboo culms of different ages contributed carbon to the shoots, but we believe that the adult culm contributed more carbon to the system, especially the 3-year-old culm; this might also be influenced by the standing conditions and bamboo stand structure.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al found that the new shoots were more abundant in unfertilised plots by unevenly applying fertiliser to the moso bamboo stand [ 14 ]; this is due to the special “rhizome–culm” system of bamboo, a typical clone of the plant, which makes the whole bamboo stand connected like multiple branches of a tree [ 15 ]. Nutrients integrated physiologically in the rhizomes are transported to the ramets together with water, affected by branching and the environment [ 16 , 17 , 18 , 19 , 20 ]. The direction of transport of substances in rhizomes is bidirectional and related to source–sink relationships, either along the rhizomes or going through rhizomes, so that parent bamboos of every age may provide nutrients for bamboo shoots [ 17 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…3F ), suggesting that the abundant recycled CO 2 was not used for starch synthesis but for other purposes. This again suggests that the starch was instead likely synthesised from sucrose produced in mature bamboo, transported in the phloem through the rhizomes and transiently stored in granules near elongating cells ( Li et al 2022 ). On the other hand, carbon derived from the breakdown of stored starch in mature bamboo organs should be 13 C-enriched, as compared to primary assimilates, because starch breakdown produced 13 C-enriched sucrose ( Gessler et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the most distributed bamboo species in China ( National Forestry and Grassland Administration, 2019 ; FAO, 2020 ), Moso bamboo grows very fast, taking only 6–8 weeks for a newly sprouted culm to finish its ~12 m height growth; such a process was named “explosive growth” ( Wang et al., 2019 ; Mei et al., 2020 ; Li et al., 2022 ). Especially the newly sprouted culms finish their height growth without leaves, which means they may primarily rely on an external supply of water ( Fang et al., 2019 ; Gu et al., 2019 ; Wu et al., 2019 ; Mei et al., 2020 ) and carbon ( Wei et al., 2019 ; Li et al., 2022 ) from other established elder culms in the leafless stage. The previous studies found that the water use patterns in the leafless and leaved stages were opposite ( Fang et al., 2019 ; Tong et al., 2021 ), characterizing peak values of the sap flux density at midnight and midday, respectively.…”
Section: Introductionmentioning
confidence: 99%